Yugārambha : Hindī kavitā kī navīnadhārā, usakā kāvya, kavīyoṃ kā paricaya tathā unakā kāvyālocana - Vājapeyī, Bhagavatīprasāda, 1899-1973 (SAMP early 20th-century Indian books project ;, 1940)
Critical study of Hindi poetry and their works.